Noise Reduction in Off-Axis Digital Holography Reconstruction from Two Reconstruction Distances Based on Talbot Effect - Cordero-Carrasco, R; Leon-Rodriguez, M; Rayas, J (Springer New York LLC, 2017)
A simple strategy based on wavefront propagation in Fresnel regime to reduce ringing effect by using an ideal filter in off-axis digital holography is presented. In addition, we demonstrate a better focusing capacity by using this ideal filter than Butterworth and Gaussian. The reconstructed and enhanced image is obtained from the averaging operation between the image at the focused image plane (z = zhd0) and the first Talbot distance order (z = zhdl). This distance is determined by the periodic ringing. Reductions of 50% of these anomalies are computed in simulation and 30% is obtained experimentally. Numerical simulations and experimental results are carried out to validate the proposal. © Springer International Publishing Switzerland 2017.